The Association Between Sensory Impairment and Adherence to COVID-19 Prevention Measures in the Adult California Health Interview Survey Population - Catherine T. Cascavita; Ahmad Santina; Ken Kitayama; Fei Yu; Victoria L. Tseng; Anne L. Coleman (Vision, 2025)
This study explores the association between vision/hearing impairment and COVID-19 prevention strategies in the 2020 and 2021 California Health Interview Survey (CHIS). This cross-sectional study used data from the 2020 and 2021 CHIS. The exposure of interest was self-reported history of sensory impairment. The outcome of interest was adherence to COVID-19 mitigation strategies defined as obtaining a COVID-19 vaccine, face mask adherence, hand washing, social distancing, and not gathering with non-household members. Logistic regression models examined the association between sensory impairment and adherence to COVID-19 mitigation strategies, controlling for age, sex, race and ethnicity, general health status, and household income. All analyses were weighted according to the CHIS sampling design. With 24,453 California adults representing 29,649,837 people, the weighted prevalence of sensory impairment was 6.1% (1,808,640/29,649,837). The regression revealed that adults with sensory impairment were 80% more likely not to maintain social distancing (odds ratio: 1.80, 95%CI: 1.03–3.13, p = 0.04) compared to those without impairment. No significant differences were found for adherence to other COVID-19 strategies. Individuals with sensory impairment may have increased difficulty with physical distancing due to their underlying impairment. Further studies are needed to explore risk reduction strategies for COVID-19 and the transmission of other infections for those with sensory impairment.